PENGARUH KEPADATAN TRAFFIC TERHADAP ON TIME PERFORMANCE DI BANDAR UDARA INTERNASIONAL JUANDA SURABAYA - Vinda Astutianingrum Diah Ayu Kusumawardani; Yuyun Suprapto; Chaeruddin (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
OTP (On Time Performance) is a condition when the departure time and arrival time of the aircraft are in accordance with what has been determined. On time performance is important because an aircraft has a use value when the aircraft is in the air. This study aims to obtain an overview of whether there is an influence between traffic density and on time performance at Juanda International Airport, Surabaya. The method used is a quantitative correlation research method. The research population is aircraft operating in 2019/2020 which contains flight data from November 2019 to February 2020 (four months). And for the sample, namely the departure plane from the population using a regional sample (cluster sampling). The data collection technique used is a documentation study containing the number of flights in the winter season. For each aircraft movement data needed for research include: EOBT (Estimated Off Block Time) and time pushback. Furthermore, the data analysis technique used is to use statistical data processing in the form of a simple linear regression test and followed by Spearman Rank correlation. The research concludes that there is a strong and inversely proportional effect between traffic density and On Time Performance at Juanda International Airport with a significance value is 0.000 and a Correlation Coefficient value is 0.687. From these results, it is hoped that there will be a review of the traffic departure density operating to reduce delays and increase on time while still complying with the On Time Performance regulations, which are calculated 15 minutes before or after Estimated Off Block Time in accordance with the rules contained in KP 112 years 2018.